EFFECT OF SAMAN JOINT TABLETS ON STRENGTH, KNEE JOINT MORPHOLOGY ON OSTEOARTHRITIS MODEL WITH MONOSODIUM IODOACETATE (Vietnam Journal of Community Medicine, 2024)
Objectives: To evaluate the effect of SAMAN joint tablets on bearing capacity, and knee morphologyin a model of osteoarthritis induced by monosodium iodoacetate (MIA).Method: 50 Wistar white rats, divided into 05 lots, 10 mice/lot: Physiological control group; 04 lots(Model/Treatment 1/Treatment 2/Reference lot) caused osteoarthritis by MIA, after 1 week of MIAinjection to mice drinking distilled water/joint SAMAN dose 476mg/kg/day and 952mg/kg /day/indomethacin.Results: SAMAN joint tablets at doses of 476mg/kg/day and 952mg/kg/day had the effect ofincreasing the distribution of weight tolerance of the hind legs (p < 0.001 and p < 0.01) comparedwith the model lot; p < 0.001 compared to before drug use); Reduces inflammatory and degenerativeknee joint damage on HE-stained knee histopathology, reduces the score of knee osteoarthritishistopathological damage (p < 0.01 compared to the model lot). These effects of SAMAN jointtablets were comparable to those of indomethacin at a dose of 2mg/kg/day.Conclusions: SAMAN joint tablets have analgesic, anti-inflammatory and anti-degenerative effectson osteoarthritis models.
Keywords: SAMAN tablets, knee osteoarthritis, rat.